Update on Helicobacter pylori infection study and key points of «Maastricht-V» consensus conference (2016) - A. A. Sheptulin; T. L. Lapina; V. O. Kaybysheva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To review in brief the reports of the XXIX international working meeting of the European Helicobacter pylori (H. pylori) and Microbiota Study Group (Magdeburg, 2016) and to discuss the key points of «Maastricht V» consensus meeting, devoted to diagnosis and treatment of infection. Key points. Association of H. pylori to both gastroenterological and non-gastrointestinal diseases and optimization of eradication therapy modes were discussed at the consensus conference. The special attention was paid for decreasing of infection burden and the stomach cancer prevention. New eradication therapy modes were presented for the regions with high and low H. pylori resistance to clarithromycin and metronidazole. It was demonstrated that clarithromycin resistance in Russia significantly varies in different regions and highest efficacy was observed for bismuth-based (in particular - bismuth tripotassium dicitrate) eradication modes. Conclusion. The guidelines of «Maastricht V» consensus meeting provide significant improvement of treatment results in H.pylori-infected patients as well as decrease of the risk of associated diseases (first of all - the stomach cancer).